PENGATURAN MATERI MUATAN MEMORANDUM OF UNDERSTANDING HELSINKI ANTARA PEMERINTAH REPUBLIK INDONESIA DAN GERAKAN ACEH MERDEKA DALAM UNDANG-UNDANG PEMERINTAHAN ACEH - Mirja Fauzul Hamdi, M. Nur Rasyid, M. Gaussyah. (Jurnal Ilmu Hukum, 2014)
Abstract: Birth of a memorandum of understanding (MoU) between the Government of Indonesia and GAM aims for a peaceful settlement of the conflict in Aceh, comprehensive, sustainable and dignified. In order to create peace in Aceh, the Indonesian government, in this case the President of Indonesia issued Presidential Instruction No. 15 of 2005 on the Implementation of the Memorandum of Understanding between the Government of Indonesia and GAM, which in turn gave birth to the Law No. 11 of 2006 on Governing Aceh. Reality is happening shows that the existence of the MoU Helsniki not recognized as a legal basis, but an option to resolve the conflict. In addition , there are several provisions in the MoU that has not been accommodated in the BAL, and also there are some rules of the implementing regulations. This study aims to analyze the reasons/ MoU chosen by the government of Indonesia and GAM as how to resolve the conflict in Aceh. As well as, to analyze the substance of the MoU has been accommodated or not in the Law on Governing Aceh . This research is normative juridical approach to the study of historical and socio-juridical . Source of data used is through the library (library research) in the form of primary legal materials, legal materials and secondary and tertiary legal materials. In addition, the data field (field research) is also used to support the literature data and to support the analysis of secondary data. Data were analyzed qualitatively that will generate data prescriptive analytical. Keywords : The substance of MoU and LoGA. Abstrak: Lahirnya nota kesepahaman (MoU) Helsinki antara Pemerintah RI dan GAM bertujuan untuk penyelesaian konflik Aceh secara damaidan berkelanjutan. Guna menciptakan perdamaian di Aceh, Pemerintah RI, dalam hal ini Presiden Indonesia mengeluarkan Inpres No. 15 Tahun 2005 Tentang Pelaksanaan Nota Kesepahaman antara Pemerintah RI dan GAM, yang pada akhirnya melahirkan Undang-Undang Nomor 11 tahun 2006 Tentang Pemerintah Aceh. Realita yang terjadi bahwa keberadaan MoU Helsinki tidak diakui sebagai dasar hukum, sehingga legalitas MoU Helsinki baik materi maupun bentuk, layak diteliti menurut hukum ketatanegaraan. Penelitian ini bertujuan untuk menganalisis legalitas materi muatan Memorandum of Understanding Helsinki antara Pemerintah RI dan GAM menurut hukum ketatanegaraan Indonesia dan konsekuensi yuridis dengan berlakunya Undang-undang Pemerintahan Aceh. Penelitian ini adalah penelitian yuridis normatif dengan pendekatan yuridis historis dan penelitian yuridis sosiologis. Sumber data yang digunakan adalah melalui kepustakaan (library research) berupa bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Selain itu, data lapangan (field research) juga digunakan untuk mendukung data kepustakaan dan untuk mendukung analisis terhadap data-data sekunder. Data yang diperoleh dianalisis secara kualitatif yang akan menghasilkan data yang bersifat preskriptif analitis. Kata kunci : Materi Muatan Nota Kesepahaman (MoU) Helsinki dan UUPA.